2022
DOI: 10.3390/app12136638
|View full text |Cite
|
Sign up to set email alerts
|

Interlocking Settlement Induced by Widening Subgrade of Railway Line

Abstract: In areas where it is difficult to secure additional land for railways, a plan to increase rail transport capacity by widening existing embankments is required. When widening the embankment, additional stress is generated at the bottom of the existing embankment, resulting in an additional settlement (interlocking settlement) of the existing embankment. Reinforced subgrade for railways (RSR) is an efficient method for widening embankments without additional sites. In this study, an existing railway embankment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…However, since the newly built subgrade and foundation have not been subjected to the long-term overburden surcharge, large settlement deformation may occur, resulting in the obvious differential settlement between the new and old subgrade [2]. In addition, it has been shown that excessive differential settlement will lead to longitudinal cracking of the joints between old and new pavement [3], thus affecting the normal operation of the roads [4,5]. Therefore, it is of great significance to study post-construction differential settlement for highway-widening projects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since the newly built subgrade and foundation have not been subjected to the long-term overburden surcharge, large settlement deformation may occur, resulting in the obvious differential settlement between the new and old subgrade [2]. In addition, it has been shown that excessive differential settlement will lead to longitudinal cracking of the joints between old and new pavement [3], thus affecting the normal operation of the roads [4,5]. Therefore, it is of great significance to study post-construction differential settlement for highway-widening projects.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there is research on how to control differential settlement [5,[24][25][26][27][28]. However, it can be found that the influence of groundwater on subgrade differential settlement is not very clear, and the control index of subgrade differential settlement is not universal.…”
Section: Introductionmentioning
confidence: 99%